a. o(0,0),w(0,b), t(h, b), s(h,0)

b. o(0,0), w(b,0), t(b, h), s(0,h)

c. o(0,0), w(0,b), t(b, h), s(h,0)

d. o(0,0), w(b,0), t(h, b), s(0,h)

It’s the first answer because if you think about it as coordinations and replace the “a” with 1 , it’s saying O(0,0), S(1,0), T(1,1) and W(0,1). And it’s figured out using simple coordination techniques

The first option: O(0,0) , S(0,a) , T(a,a) , W(a,0)

Step-by-step explanation:

Point O : is the intersection between x-axis and y-axis ⇒ (0,0)

Point W : is falling over the x-axis, OW = length of the square = a ⇒ (a,0)

Point S : is falling over the y-axis, OS = length of the square = a ⇒ (0,a)

Point T : WT = a and SW = a ⇒ (a,a)

Option 2. is the right answer.

Step-by-step explanation:

In the given question we have to find the coordinates of O, W, Y, S.

Length of OW = YS = b and length of YW = OS = h

For Point O

Since point O is the origin then it's coordinates will be (0, 0).

For point W

Length of OW = b at x axis and length on y axis is 0. Then the coordinates will be (b, 0)

For point Y

Length of WY on y axis = h and length of SY on x axis = OW = b

Therefore coordinates of Y will be (b, h).

For point S

Length of OS on y axis = h and x axis is 0.Therefore the coordinates will be (0, h)

Therefore Option 2 is the right answer.

(f * g)(2) = (2x^2 - 10)(x + 9) First step is to FOIL the binomials2x^3 + 18x^2 - 10x - 90 Next, Plug 2 in for each 'x'2(2)^3...Read More

2 more answers

A works because 1 • 4 + 1.5 • 4 = 10 and 1 • 6 + 1.5 • 6 = 15...Read More

2 more answers

5x + 5step-by-step explanation: you should always add the diagrams and graphs we cannot see. this particular question is kind of borderline because we can make a graph for you.(f +...Read More

1 more answers

This isn't true because the exact answer of a system is where the lines cross each other, not where they cross a grid....Read More

3 more answers

= 1 This means that the probability of event A or event B of happening is 1 or certainly would happen....Read More

2 more answers

[tex]f(x) = 3x {}^{2} \\ \\ g(x) = x + 2 \\ \\ (f.g)(x) \\ \\ 3(x + 2) {}^{2 } \\ \\ 3(x {}^{2} + 4 + 4x)[/tex]...Read More

2 more answers

1. a^3 / bFor the exponents of a: a^4/a^1 = a^(4-1) = a^3For the exponents of b: b^-3 / b^-2 = b^(-3--2) = b^-1 = 1/b2. y^8 / x^2For the exponents of y: (y^-4)^-2 = y^(-4*-2) = y^8...Read More

2 more answers

- Plz answer what is the equation of the function shown in the graph? a...
- Rewrite each quadratic equation in standard form by expanding the bino...
- Can someone solve #4 and explain it? i really appreciate it on this p...
- What is the approximate volume of the sphere? use 3.14 to approximate...
- Which rule describes the composition of transformations that maps figu...
- The johnson twins were born two years after their older sister. this y...
- Use the inequality 10cosx≥0 with a period [−2π,0] to answer the follow...
- What are the solutions to the system of equations graphed below...
- What is another name for counting numbers...
- Use the expression 5(6 + 4x) to answer the following: part a: descri...